Laparoscopic surgery for gallstones or common bile duct stones: A stably safe and feasible surgical strategy for patients with a history of upper abdominal surgery - Yang, Shaojie; Wu, Shuodong; Dai, Wanlin; Pang, Liwei; Xie, Yaofeng; Ren, Tengqi; Zhang, Xiaolin; Bi, Shiyuan; Zheng, Yuting; Wang, Jingnan; Sun, Yang; Zheng, Zhuyuan; et al. (Frontiers in Surgery, 2022)
A history of upper abdominal surgery has been identified as a relative contraindication for laparoscopic surgery. This study aimed to compare with the clinical efficacy and safety of laparoscopic cholecystectomy (LC) and laparoscopic common bile duct exploration (LCBDE) in patients with and without previous upper abdominal surgery. The preoperative liver function indexes showed no significant difference between the observation groups and the control groups. For patients underwent LC, group A and group B had more abdominal adhesions than control group. 1 case was converted to open in group A and 1 case in group B respectively. There was no statistically difference in operation time, estimated blood loss, postoperative hospital stay, and drainage volume. For patients underwent LCBDE, group C and D had more estimated blood loss than control group (group C, 41.33±50.84 vs. 18.97±13.12 ml, p=0.026; group D, 66.11±87.46 vs. 18.97±13.12 ml, p=0.036). Compared with control group, group C exhibited higher longer operative time (173.87±60.91 vs. 138.38±57.38 minutes, p=0.025), higher drainage volume (296.83±282.97 vs. 150.83±127.04 ml, p=0.015), longer postoperative hospital stay (7.97±3.68 vs. 6.17±1.63 days, p=0.021). There was no mortality in all groups. The surgical strategy of LC or LCBDE is still safe and feasible for experienced laparoscopic surgeons to perform on the patients with previous upper abdominal surgery.